DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS BANJARBARU - Karmila; Herawati; Lestari, Dhian Ririn (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Family support is needed by people with mental disorders in motivating them for care andtreatment. Things that can trigger a recurrence and prolong the treatment of other psychiatricdisorders among patients not taking medication regularly.Objective this research aims to analyzeand determine the relationship of family support with drink medicine obediently of mentaldisorder patient. Methods of this research was correlational with cross-sectional study design.Respondents were 35 patient, instruments used in the form of family support questionnaire anddrink medicine obediently questionnaire. Results this research showed that 42.86% gave goodfamily support, 37.14% providing sufficient family support and 20% provide less support.Medication adherence in patients with mental disorders who dutifully 24 respondents (68.57%)and non-adherent patients 11 respondents (31.43%). Analysis of the research data usingspearman correlation test with p value of 0.000, which means p ˂ 0.05, so there was a significantrelationship between family support with medication adherence in patients with mental disordersin Puskesmas Banjarbaru with r = 0.748, which means strength strong relationships and have apositive direction. The family was expected to gave a good family support to patients with mentaldisorders that adherent patients taking medication to cure and prevent recurrence